Pelatihan Pembuatan RPS Berbasis OBE bagi Dosen Fakultas Pertanian dan Kehutanan Universitas Muhammadiyah Palangkaraya: Training on OBE-based RPS Development for Lecturers of Faculty of Agriculture and Forestry, Muhammadiyah Universitas of Palangkaraya - Rahmaniati, Rita; Rosawanti, Pienyani; Mariaty, Mariaty; Purnama, Ardiyansyah; Hariyadi, Hariyadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Semester Lecture Plan based on outcome-based education (RPS OBE) as a lecture plan that is in line with the Independent Curriculum by emphasizing student-centered learning processes so that learning occurs interactively and innovatively so that graduating students have high competence and are flexible to follow current developments in line with the expectations of the industrial revolution 4.0. This service activity aims to increase the competence of lecturers in preparing the OBE RPS. The methods used are lecture, question and answer, discussion and practice. This activity had a positive impact on Fapertahut lecturers, which is marked by an increase in compiling CPMK before activities are carried out with CPMK which is produced at the end of the activity. Presentation and mentoring activities are able to correct errors in understanding in the theory session regarding RPS OBE. By practicing and presenting, the target audience will more quickly recognize mistakes made. Apart from that, presentations and discussions can become material for reflection and reference for other participants.